Demonstration and Scaling of Integrated Management of Parasitic Weeds on Faba bean in Ethiopia, Morocco and Tunisia - Kassaw, Admasie; Awol, Mohammed; Seyoum, Negussie; Asefie, Seyoum; Kharrat, Mohamed; Abbes, Zouhaier; Dedoui, Arij; Maafa, Ilyass; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2024)
Parasitic weeds (Orobanche spp.) severely hinder food legume production in the Mediterranean and East African highlands. To combat this issue, a multi-pronged approach was implemented in Ethiopia, Tunisia, and Morocco during the 2023/24 cropping season. This strategy involved integrating partially resistant faba bean varieties with sub-lethal herbicide application and mixed cropping techniques. In Ethiopia, the combined application of sub-lethal herbicides and fungicide seed treatments significantly boosted faba bean productivity, with widespread adoption by both male and female farmers. In Tunisia and Morocco, Corum herbicide application effectively reduced parasitic weed infestation on faba bean crops. To further drive innovation, the production of early-generation seeds of partially resistant varieties should be facilitated in Ethiopia and Tunisia. Additionally, exploring mixed cropping crops within the cropping system, as well as validating the use of Curum herbicide to control both parasitic and non-parasitic weeds in North Africa, are crucial steps for the 2024/25 cropping season."